Let's compute the two factors separately: as for "the sum of -13/5 and 12/7", we have to rewrite the two fractions so that they have the same denominator. Since the least common multiple of 5 and 7 is 35, we will change both fractions so that they have denominator 35:
![(-13)/(5) = (-13)/(5)(7)/(7) = (-91)/(35) \qquad \qquad (12)/(7) = (12)/(7)(5)/(5) = (60)/(35)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/8epjgcq2f61bqh7xzgqheg6j90s224nrdp.png)
So now we can sum them:
![(-13)/(5)+(12)/(7) = (-91)/(35)+(60)/(35) = (-91+60)/(35) = (-31)/(35)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/po5y20mn7u7hclwrfdgi7hs5enkhq1pgti.png)
Multiplication is easier, since you just have to multiply numerators and denominators with each others:
![(-31)/(7) (-1)/(2) = (-31 \cdot (-1))/(7\cdot 2) = (31)/(14)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/q4bvhvxhbrzu996qeal7k1lg3f461p86os.png)
Finally, we must divide the two fractions. Dividing by a fraction is the same this as multiplying by the inverse of that fraction, i.e. we have to switch numerator and denominator:
![(-31)/(35) / (31)/(14) = (-31)/(35) \cdot (14)/(31) = -(2)/(5)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/fgtywsmd5461fecrzthw3jmoazb77nbd5e.png)